Test and Analysis of the Influence of Polish Grinding Technology on Wear Performance of Gear Running Stage - Guangxiang Zhang; Yushuang Li; Xu Zhang (Jixie chuandong)
The wear of gear in running stage can reflect the fatigue life and wear performance of gear in the whole service cycle. Polishing and grinding technology is a new type of gear grinding technology，which can effectively improve the surface quality of gears and improve the wear performance of gears in running stage. To investigate the effect of polishing and grinding technology on the running performance of gears and taking a low-speed driving gear of a transmission as the research object，a pair of polishing grinding gears and a pair of conventional grinding gears are processed respectively. The two pairs of gears are tested on the gear test stand. The ferrogram is collected during the gear operation. The ferrograph data is analyzed by using Matlab，and the influence law of polishing and grinding process on the running performance of gear is obtained. The results show that the polishing grinding technology can effectively improve the wear performance of the gear in the running process，reduce the wear rate of the gear，shorten the running cycle of the gear，and make the wear process of the gear in the running process more moderate. The conclusion provides some data support and reference for the application of this technology in gear machining.